SWOT Analysis of Reverse Brain Drain Regulation for Excellent Human Resources to Support Indonesia’s Non-Military Defense - Hari Prasetyo; Adnan Madjid; Joni Widjayanto; Robby Mochammad Taufik (Ilomata International Journal of Social Science, 2026)
This study examines the persistent issue of brain drain in Indonesia and its underexplored link to non-military defense policy, offering a novel thematic perspective. It aims to assess the effectiveness of existing reverse brain drain regulations, identify implementation barriers, and propose evidence-based strategies to enhance policy attractiveness. Using a Systematic Literature Review (SLR) and SWOT analysis, the study synthesizes dispersed policies to evaluate their strengths, weaknesses, opportunities, and threats. The findings reveal fragmented regulations, limited career incentives, and inadequate research facilities as major obstacles rooted in policy gaps and weak institutional coordination. The study recommends targeted incentives, clearer legal frameworks, and stronger policy alignment to support human capital development as part of Indonesia’s non-military defense strategy.